PRAKTIK PENGALAMAN LAPANGAN KONSTITUSI AGAMA ISLAM DAN ISTIQOMAH DALAM BERAGAMA - Hadiri, Hadiri (Sindoro: Cendikia Pendidikan, 2024)
This study examines the implementation of Islamic religious constitution and strategies for enhancing religious consistency (istiqomah) in the Primary School Teacher Education (PGMI) Study Program at Sunan Giri University, Surabaya. Employing a qualitative descriptive method with a case study approach, the research involves participatory observation, in-depth interviews, and documentary study. Results indicate that the implementation of Islamic religious constitution has progressed positively, albeit requiring enhancement in substantive understanding. Factors influencing students' religious consistency include family environment, peer interactions, and social media influence. The success of the teaching practicum (PPL) is supported by intensive guidance and active student participation, despite challenges such as varying student abilities and time management issues. Solutions implemented include interpersonal approaches and reward systems. This research highlights the importance of integrating religious values in higher education to shape strong student character responsive to global challenges. Penelitian ini mengkaji implementasi konstitusi agama Islam dan strategi peningkatan istiqomah beragama di lingkungan Program Studi Pendidikan Guru Madrasah Ibtidaiyah (PGMI) Universitas Sunan Giri Surabaya. Menggunakan metode kualitatif deskriptif dengan pendekatan studi kasus, penelitian ini melibatkan observasi partisipatif, wawancara mendalam, dan studi dokumentasi. Hasil menunjukkan bahwa implementasi konstitusi agama Islam telah berjalan positif, namun masih memerlukan peningkatan pemahaman substantif. Faktor-faktor yang mempengaruhi istiqomah beragama mahasiswa meliputi lingkungan keluarga, pergaulan teman sebaya, dan pengaruh media sosial. Keberhasilan pelaksanaan PPL didukung oleh bimbingan intensif dan partisipasi aktif mahasiswa, meskipun terdapat hambatan seperti perbedaan kemampuan mahasiswa dan manajemen waktu. Solusi yang diterapkan meliputi pendekatan interpersonal dan sistem reward. Penelitian ini menyoroti pentingnya integrasi nilai-nilai keagamaan dalam pendidikan tinggi untuk membentuk karakter mahasiswa yang kuat dan responsif terhadap tantangan global.